Competencies of Travel Department Students in e-Commerce- Based Business - Yenni Susanto; Mukarramah Machmud; Darmayasa Darmayasa; Masri Ridwan; Aris Baharuddin (Universitas Negeri Makassar, 2022)
Contributing to research on industrial revolution 4.0 era , this study investigates e-commerce practices carried out by tourist travel businesses in relation to the preparation of human resources in the tourism education sector. Key informant managers in two cities, Bali and Yogyakarta were interviewed to explore their adopted employee training and development models. The resulting data, triangulated by informal observation and document study, were analyzed using a theoretical framework that emphasizes seven indicators of interdependent employee development. The findings indicate that the global-oriented education management will be able to answer various needs in the job market through curriculum reconstruction with a digital human approach.